Effects of Ureaplasma urealyticum infection on semen quality and sperm morphology - Xianchun, Fu; Jun, Fang; Zhijun, Dai; Mingyun, Hong (Frontiers in Endocrinology, 2023)
Introduction: Ureaplasma urealyticum (U. urealyticum) infection is primarily associated with damage to male fertility through its effects on male sperm parameters. However, its effects on sperm semiological variables remain unclear. Therefore, this study aimed to investigate whether U. urealyticum infection was associated with semen quality and sperm morphology. Methods: From 2019 to 2021, this cross-sectional study analyzed infective pathogens and semen variables in 1064 males (22–30 years old) recruited from our reproductive center and the general public. Routine semen parameters and normal sperm morphology rate were analyzed using methods outlined by the World Health Organization. The associations between semen quality, sperm morphology, and U. urealyticum infection were studied using general linear models. Results: The participants were categorized into three groups: (i) U. urealyticum infection (n=328), (ii) non-U. urealyticum infection (including males with urogenital tract infection symptoms but no U. urealyticum detected in their semen samples, n=377), and (iii) normal volunteers (males without symptoms of urogenital tract infection and no pathogens detected in semen samples, n=359). U. urealyticum in semen samples was observed to be associated with lower sperm concentrations (p<0.001) and a lower ratio of anterograde motile spermatozoa (p<0.001). Semen cultures positive for U. urealyticum were associated with lower normal sperm morphology (p<0.001) compared to semen cultures negative for U. urealyticum. Conclusion: This study shows the importance of proper investigations for U. urealyticum during routine clinical examinations and diagnoses of males with infertility.